Cardiological society of India document on safety measure during echo evaluation of cardiovascular disease in the time of COVID-19 - Rakesh Gupta; Mrinal Kanti Das; P.P. Mohanan; Pradip K. Deb; S.K. Parashar; H.K. Chopra; Sameer Shrivastava; Santanu Guha; Kewal C. Goswami; Rakesh Yadav; R. Alagesan; V. Amuthan; et al. (Indian Heart Journal, 2020)
An echocardiographic investigation is one of the key modalities of diagnosis in cardiology. There has been a rising presence of cardiological comorbidities in patients positive for COVID-19. Hence, it is becoming extremely essential to look into the correct safety precautions, healthcare professionals must take while conducting an echo investigation. The decision matrix formulated for conducting an echocardiographic evaluation is based on presence or absence of cardiological comorbidity vis-à-vis positive, suspected or negative for COVID-19. The safety measures have been constructed keeping in mind the current safety precautions by WHO, CDC and MoHFW, India.